Photovoltaic materials: Cu2ZnSnS4 (CZTS) nanocrystals synthesized via industrially scalable, green, one‐step mechanochemical process. (23rd June 2019) - Baláž, Peter; Hegedus, Michal; Baláž, Matej; Daneu, Nina; Siffalovic, Peter; Bujňáková, Zdenka; Tóthová, Erika; Tešínsky, Matej; Achimovičová, Marcela; Briančin, Jaroslav; Dutková, Erika; Kaňuchová, Mária; et al.
Abstract: The present study demonstrates a scalable approach towards the pure Cu2 ZnSnS4 (CZTS) phase starting from microsized Cu, Zn, Sn, and S mixture or a combination of nanosized CuS, SnS plus microsized Zn and S. A set of mechanochemical reactions was carried out in an industrial vibratory mill. The pure CZTS phase was obtained after 360 minutes of milling with an average crystallite size of 15 nm for both mixtures. The kinetics of CZTS formation was investigated following the X‐ray diffractometry (XRD) patterns of the reaction mixtures milled for various times. The morphology of particles and their elemental composition was studied by scanning electron microscopy (SEM)/transmission electron spectroscopy (TEM) and EDX analysis. Photoelectron spectroscopy (XPS) analysis showed the presence of Cu +, Zn 2+, Sn 4+, and S 2− species on the surface of CZTS with only minor oxidation. Thermal stability of the synthesized materials was followed by thermogravimetric analysis. Based on UV‐VIS measurements, the calculated bandgap E g  = 1.44 to 1.50 eV of the synthesized CZTS samples is acceptable for photovoltaic application. Moreover, the applied mechanochemical approach can produce 100 to 500 g of CZTS in a batch mode experiment that is 10 to 50 times higher amount as the throughput of laboratory planetary mills. Hypothetically, in the applied industrial eccentric vibratory mill, the amount can be increased up to 50 kg per one batch. Abstract : Cu2 ZnSnS4 (CZTS) phase was successfully synthesized by solid‐state process from elements and/or compounds. The synthesis was carried out in an industrial mill with the capability to produce from hundred grams up to kilograms of kesterite per batch. The prepared samples with their band gap 1.44 to 1.50 eV are acceptable as absorbers for photovoltaic application.